Preliminary Screening for Microplastic Concentrations in the Surface Water of the Ob and Tom Rivers in Siberia, Russia - Yulia A. Frank; Egor D. Vorobiev; Danil S. Vorobiev; Andrey A. Trifonov; Dmitry V. Antsiferov; Tina Soliman Hunter; Scott P. Wilson; Vladimir Strezov (Sustainability, 2020)
To date, the largest Russian rivers discharging to the Arctic Ocean remain a “blank spot” on the world map of data on the distribution of microplastics in freshwater systems. This study characterizes the abundance and morphology of microplastics in surface water of the Ob River and its large tributary, the Tom River, in western Siberia. The average number of particles for the two rivers ranged from 44.2 to 51.2 items per m3 or from 79.4 to 87.5 μg per m3 in the Tom River and in the Ob River, respectively. Of the recovered microplastics, 93.5% were less than 1 mm in their largest dimension, the largest group (45.5% of total counts) consisted of particles with sizes range 0.30–1.00 mm. Generally, microfragments of irregular shape were the most abundant among the Ob and Tom samples (47.4%) and exceeded microfibers (22.1%), microfilms (20.8%), and microspheres (9.74%) by average counts. Results from this study provide a baseline for understanding the scale of the transport of microplastics by the Ob River system into the Arctic Ocean and add to currently available data on microplastics abundance and diversity in freshwater systems of differing global geographic locations.